Fusobacterium Nucleatum : An Atypical Cause of Pyogenic Liver Abscess in an Apparently Immunocompetent Patient - AR, Yusoff; NA, Abd Razak; S, Samsuddin; S, Mokhtar (IIUM Medical Journal Malaysia, 2021)
Pyogenic liver abscess is an uncommon but potentially lethal infection if left untreated. Enteric bacteria and anaerobes are the most common causative organisms of pyogenic liver abscess. Although most infections are of a polymicrobial nature, monomicrobial infections are possible. An immunocompromised status and the presence of periodontal disease are the risk factors for liver abscess caused by these rare, monomicrobial anaerobic infections. Here, we report on a successful non-operative management of a case of multiloculated pyogenic liver abscess caused by Fusobacterium nucleatum in a young, healthy, immunocompetent male patient. The diagnosis was established by radiological imaging and was based on a positive aspirate culture, whereas the mainstay of treatment comprised percutaneous drainage and a prolonged course of antibiotics. Thus, the patient was successfully treated with a 2-week course of intravenous imipenem/cilastatin while he was on percutaneous drainage, and he is now doing well.